Selected Acoustic Features of the Welsh Lateral Fricative /ɫ/ - Baran, Michał (Research in Language, 2024)
The Welsh language exhibits a number of features uncommon from a cross-linguistic point of view, one of which is a relatively large number of fricative phonemes. This paper analyses selected acoustic features of the Welsh lateral fricative /ɬ/ in order to contribute to the debate on the laryngeal system in Welsh and the classification of /ɬ/ within that system. Total articulation length, voicing length and SMA parameters of the friction period are measured and analysed on the basis of recordings of 6 native speakers of Welsh. The results confirm the classification of /ɬ/ as a fortis sound proposed in earlier studies (Asmus and Grawunder 2017, Baran forthcoming) and suggest that the Welsh /ɬ/ may exhibit aspiration.